2016
DOI: 10.1148/radiol.2015150768
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Resting-State Functional Connectivity in the Human Spinal Cord at 3.0 T

Abstract: Purpose To apply resting-state functional magnetic resonance (MR) imaging to map functional connectivity of the human spinal cord. Materials and Methods Studies were performed in nine self-declared healthy volunteers with informed consent and institutional review board approval. Resting-state functional MR imaging was performed to map functional connectivity of the human cervical spinal cord from C1 to C4 at 1 × 1 × 3-mm resolution with a 3.0-T clinical MR imaging unit. Independent component analysis (ICA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 17 publications
(17 reference statements)
6
53
0
Order By: Relevance
“…Once the components are identified, these can then be removed from the data (for task-based data, this should be done by including their time-courses as covariates in the design matrix). Such an approach has been taken in a recent resting-state spinal fMRI study (San Emeterio Nateras et al, 2016), as well as in a task-based study on motor-learning where the authors also explicitly listed their criteria for designating a component as noise (Vahdat et al, 2015). It is furthermore possible to combine ICAbased denoising with the model-based approaches described earlier; such an approach has recently been shown beneficial for brainstem data (Faull et al, 2016) and might hold potential for spinal fMRI as well.…”
Section: Discussionmentioning
confidence: 99%
“…Once the components are identified, these can then be removed from the data (for task-based data, this should be done by including their time-courses as covariates in the design matrix). Such an approach has been taken in a recent resting-state spinal fMRI study (San Emeterio Nateras et al, 2016), as well as in a task-based study on motor-learning where the authors also explicitly listed their criteria for designating a component as noise (Vahdat et al, 2015). It is furthermore possible to combine ICAbased denoising with the model-based approaches described earlier; such an approach has recently been shown beneficial for brainstem data (Faull et al, 2016) and might hold potential for spinal fMRI as well.…”
Section: Discussionmentioning
confidence: 99%
“…Through the Statistical Parametric Mapping 8 (SPM8, http://www.fil.ion.ucl.ac.uk/spm/) and Resting-State fMRI Data Analysis Toolkit (REST, http://restfmri.net/forum/index.php) toolboxes in MATLAB 7.11.0 (Mathworks, Natick, MA, USA), the raw EPI images were processed for slice timing, motion correction, nuisance regression, detrend, and band-pass filtering (0.01–0.08 Hz). Regressors included: 1) cerebrospinal fluid (CSF) pulsation signal and tissue motion signal that was extracted through independent component analysis (ICA) through gift (http://mialab.mrn.org/software/gift/) toolbox; 2) motion correction parameters (x and y translation)[12]. The first 10 volumes were discarded to exclude the initial transient effects.…”
Section: Methodsmentioning
confidence: 99%
“…RsfMRI focused on low-frequency blood oxygen level-dependent (BOLD) fluctuations which are considered to reflect intrinsic neural activity. In recent years, rsfMRI has already been introduced in spinal cord studies and revealed that the spinal cord is intrinsically organized [1012]. …”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord Resting‐State functional magnetic resonance imaging (rsfMRI) is a promising technique that offers a new way to investigate intrinsic spinal cord function in health and disease . However, several technical challenges still hamper its clinical application.…”
mentioning
confidence: 99%
“…However, several technical challenges still hamper its clinical application. Recent studies have adopted adjustments to rsfMRI image acquisition to successfully overcome challenges such as the small size of the spinal cord and susceptibility artifacts . One key problem that remains is non‐ignorable physiological noise …”
mentioning
confidence: 99%